2022
DOI: 10.1177/26317745221076705
|View full text |Cite
|
Sign up to set email alerts
|

Current endoscopic closure techniques for the management of gastrointestinal perforations

Abstract: Acute gastrointestinal perforations occur either from spontaneous or iatrogenic causes. However, particular attention should be made in acute iatrogenic perforations as timely diagnosis and endoscopic closure prevent morbidity and mortality. With the increasing use of diagnostic endoscopy and advances in therapeutic endoscopy worldwide, the endoscopist must be able to recognize and manage perforations. Depending on the size and location of the defect, a variety of endoscopic clips, stents, and suturing devices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Statistical studies have demonstrated that different surgical approaches for perforated duodenal ulcers have significant differences regarding recovery, complications, and mortality rates [13][14][15][16]. Upon comparison between conventional approaches (open abdominal) versus minimally invasive (laparoscopic) and between the varying procedures (omental patch, suturing, and E-VAC), our case report demonstrates that the E-VAC system is the option with the best prognosis and lowest mortality rate [17][18][19][20][21][22][23][24][25][26][27]. Without the use of the E-VAC system, this patient with an ASA score of IV did not have a favorable prognosis, having a high risk of postoperative mortality [3,[16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Statistical studies have demonstrated that different surgical approaches for perforated duodenal ulcers have significant differences regarding recovery, complications, and mortality rates [13][14][15][16]. Upon comparison between conventional approaches (open abdominal) versus minimally invasive (laparoscopic) and between the varying procedures (omental patch, suturing, and E-VAC), our case report demonstrates that the E-VAC system is the option with the best prognosis and lowest mortality rate [17][18][19][20][21][22][23][24][25][26][27]. Without the use of the E-VAC system, this patient with an ASA score of IV did not have a favorable prognosis, having a high risk of postoperative mortality [3,[16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 78%
“…Upon comparison between conventional approaches (open abdominal) versus minimally invasive (laparoscopic) and between the varying procedures (omental patch, suturing, and E-VAC), our case report demonstrates that the E-VAC system is the option with the best prognosis and lowest mortality rate [17][18][19][20][21][22][23][24][25][26][27]. Without the use of the E-VAC system, this patient with an ASA score of IV did not have a favorable prognosis, having a high risk of postoperative mortality [3,[16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Not only was the patient able to recover, but the patient was able to do so without any complications and with rapid recovery.…”
Section: Discussionmentioning
confidence: 95%
“…The estimated annual rate of perforations has increased owing to the popularity and expansion of endoscopy 1 . GIT perforation is a rare and unexpected life-threatening complication associated with a high mortality rate (6–33%) 2 . Furthermore, perforations in the stomach predominantly arise from the worsening of preexisting conditions (peptic ulcers, obstructions, and malignancies), anastomotic leakage after gastrectomy, and iatrogenic causes, including endoscopy-related procedures [endoscopic mucosal resection (EMR), endoscopic submucosal dissection (ESD), polypectomy], and foreign bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Sutures and staples are considered the “gold standard” for open surgery wound closure [ 8 ]. To better adapt to minimally invasive techniques, laparoscopic or endoscopic closures of GI wounds utilize metal clips, stents, or suturing devices for different sizes and locations of GI defects [ 9 ]. Despite the excitement surrounding the early evidence concerning minimally invasive closure techniques, there are many inherent disadvantages associated with suture-based tissue sealing that include: (1) secondary damage to tissue due to needle piercing; (2) complicated, time-consuming technical processes that require high surgical skills; (3) insufficient containment of fluid leaks; and (4) infection, inflammation, and delayed healing at the site [ 6 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…To better adapt to minimally invasive techniques, laparoscopic or endoscopic closures of GI wounds utilize metal clips, stents, or suturing devices for different sizes and locations of GI defects [ 9 ]. Despite the excitement surrounding the early evidence concerning minimally invasive closure techniques, there are many inherent disadvantages associated with suture-based tissue sealing that include: (1) secondary damage to tissue due to needle piercing; (2) complicated, time-consuming technical processes that require high surgical skills; (3) insufficient containment of fluid leaks; and (4) infection, inflammation, and delayed healing at the site [ 6 , 8 , 9 , 10 , 11 ]. Therefore, there is a substantial interest and need for the development of atraumatic, minimally invasive, and easy-to-apply GI wound closure technologies to provide fluid-tight sealing and promote wound healing for different types of GI defects.…”
Section: Introductionmentioning
confidence: 99%